2013
DOI: 10.1007/978-3-642-40480-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-Based Reading and the Place of E-Books in Everyday Life

Abstract: Abstract. With the proliferation of digital reading technologies and their underlying ecosystem, practices of reading are currently undergoing significant changes. Despite the currency of the topic, we find there is little empirical research on how people incorporate digital reading technologies into their existing leisure-based reading practices. In this paper, we explore the place of ereading for pleasure in daily life, and how it is co-evolving with practices surrounding printed books. We present a diary st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
1
20
1
4
Order By: Relevance
“…On one hand, our findings support existing research on reading in that we also found that physical books have values that e-books or audiobooks don't have, such as providing the possibility to arrange them in libraries (e.g., [19]), or that the form factor of e-book readers (e.g., lightweight, mobile) influences how and when they are used (e.g., [22]). On the other hand, our findings also add to the existing body of research.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…On one hand, our findings support existing research on reading in that we also found that physical books have values that e-books or audiobooks don't have, such as providing the possibility to arrange them in libraries (e.g., [19]), or that the form factor of e-book readers (e.g., lightweight, mobile) influences how and when they are used (e.g., [22]). On the other hand, our findings also add to the existing body of research.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, Hupfeld et al have, by means of diary studies, intensively investigated people's practices with e-books, finding, among others, that people would choose printed books if the books mattered to them while digital books were rather seen as transitory. Further, e-books were not considered to replace physical books [22]. Additionally, Hupfeld et al interviewed people about their temporal, spatial, material, and social practices with books, demonstrating that books are more than reading devices, such as placing books around them for comfort or augmenting them to create traces.…”
Section: Reading Experiencementioning
confidence: 99%
“…These results are in line with the results of previous study by Colombo et al [3] that investigated "where" and "when" children read paper books. Thus, it seems that children's practices surrounding paper books are not much affected by the use of digital reading technology -contrarily to what observed by Hupfeld et al [6] with adults. One should be careful in generalizing the findings of this exploratory study, as they are limited to the specific case of tablets used for leisure reading by children.…”
Section: Discussioncontrasting
confidence: 44%
“…The symbolic aspect of reading in public spaces is important for readers, as they worry about how their actions will be interpreted, from the mere activity of reading to the content chosen. Our participants highlight that smartphones give them unprecedented privacy, as they don't need to worry about what others will think about them reading or about what they are reading (see also Hupfeld et al, 2013). The social dimension comes into play in different ways.…”
Section: Reading In Non-dedicated Settings Outside Homementioning
confidence: 95%